Middle classes and rurality: The expansion of urban middle classes and new social inequalities in Colombia (2017)
In this article I analyse the relationship between rurality and middle classes. Few recent studies on middle classes have examined the role of rurality within middle class expansion processes at the global scale. I conducted a critical analysis of rurality and the middle classes in light of a recent proliferation of studies on global middle classes. This proliferation may be reflective of an evolving political and academic discourse within mainstream institutions, aimed at promoting the expansion of urban middle classes. Consequently, a critical analysis of this political and academic discourse attending to the various impacts of the expansion of urban middle classes on nature, and on rural areas and populations, is required. I applied mixed research methods in a case study of Colombia. The results indicated a paradox inherent in the expansion of middle classes. On the one hand, this expansion is aimed at reducing general social inequalities, and yet, on the other hand, it increases rural (and urbanrural) inequalities. Moreover, the expansion of urban middle classes reproduces land concentration and has negative impacts on nature. Concurrently, connections between urban and rural populations, along with new ruralities encompassing urban middle class populations, are evolving under the banner of sustainability. These trends reflect the complexity of structures of inequality in the connections between rural and urban populations. © 2017 Mattersburger Kreis fur Entwicklungspolitik. All rights reserved.